Application of the waterfall method in the design of a sales distribution system CV. Semakin Jaya Java Based - Han Sulaiman; Nasrulloh Isnain; Ardhi Dinullah Baihaqie (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
CV Semakin Jaya is a company engaged in the sale of food, beverages, and other household goods. CV Semakin Jaya prioritizes comfortable and satisfying service. Buying and selling services always keep up with the times, prioritizing quality and good service for the general public. In this research, we try to create a system to be able to handle various problems that occur, for example, overcoming errors due to human negligence in counting as well as the ability to maintain and speed in ongoing production. Besides that, the storage of data is less regular and the presentation of information and reports on production and distribution is less effective for the company. By using the Waterfall Method a systematic and sequential approach. The stages of the waterfall model include requirements, design, implementation, verification and maintenance. The waterfall method is suitable for projects to create new systems and also large-scale system or software development